FACTORS RELATED TO THE EVENT STUNTING IN CHILDREN IN THE WORK AREA OF THE SIULAK GEDANG PUSKESMAS, KEINCI REGENCY YEAR 2022 - Niken Anggraini; Abul Ainin Hapis; Subakir Subakir (Sekolah Tinggi Pariwisata Mataram, 2023)
Stunting is a condition of children who have a relatively low length or height compared to their age, which can be measured by child anthropometry according to the Ministry of Health in 2020. Children are said to be Stunting if they have a z-score value of <-2 Standard Deviation. Stunting can be caused by several factors such as child nutrition problems, social conditions, economy, infectious diseases, poor environmental sanitation, education, income, knowledge and others. The prevalence of stunting in Jambi Province reached 22.4% in 2021, including Kerinci Regency which is one of the contributors to the Stunting rate in Jambi Province. There are 10 Stunting Loci in Kerinci Regency including the work area of the Siulak Gedang Health Center with a total of 63 toddlers who experienced Stunting in 2020. So researchers are interested in looking for the relationship of several stunting risk factors in the region. This research method is quantitative with the case control research design of a study sample of 72 respondents, with a ratio of 1:1 (36 Case and 36Control) with the criteria of mothers who have children aged 24-59 months. Data were obtained by conducting interviews using questionnaires, the study was conducted from May 09 to June 04, 2022. The data were analyzed using univariate and bivariate methods using the chi-square test. The results of this study prove the relationship between Diarrhea (p-value=0.009 OR=4.02 CI95%=1.50-10.74), BBLR (p-value=0.000 OR = 10.5 CI 95%= 3.53-31.2), and Maternal Knowledge (p-value=0.058 OR=2.8 CI95%=1.07-7.3) to the incidence of Stunting in toddlers. There is no relationship between Exclusive Breastfeeding (p-value=0.637 OR=0.72 CI95%=0.28-1.81) and the incidence of Stunting in toddlers.